The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jocs.12387
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Percutaneous Stenting of Superior Vena Cava Obstruction Following Heart Transplantation in Adult Patients with Pacemaker Leads

Abstract: Vena cava superior syndrome is a serious complication after heart transplantation, leading to low cardiac output, cerebral edema, and multi-organ dysfunction. We report three adult patients who underwent heart and heart-lung transplantation and required immediate postoperative balloon angioplasty and stent placement by interventional radiology. The observed obstructions were located at sites of intraoperatively removed pacemaker or defibrillator wires. Percutaneous stent placement immediately improved the hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Percutaneous stent placement provided immediate improvement to the hemodynamic condition of the patients. 17 A registry-based study of heart transplant patients showed an overall incidence of 3% with 32% of these patients with a history of cavopulmonary anastomosis prior to transplant. 18 Although systemic veins in the superior distribution appear to be more commonly involved, obstruction to the IVC has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous stent placement provided immediate improvement to the hemodynamic condition of the patients. 17 A registry-based study of heart transplant patients showed an overall incidence of 3% with 32% of these patients with a history of cavopulmonary anastomosis prior to transplant. 18 Although systemic veins in the superior distribution appear to be more commonly involved, obstruction to the IVC has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This places the patient at risk for complications at the anastomotic site, specifically stenosis and thrombosis with the potential for acute superior vena cava (SVC) obstruction . Several treatment modalities for acute SVC obstruction following solid organ transplant have been considered, including thrombolysis (drug and mechanical), angioplasty, and stenting . There is a single report of rheolytic thrombolysis with stent implantation utilized in a 37‐yr‐old patient for acute SVC obstruction 11 days after a heart–lung transplant for cystic fibrosis.…”
mentioning
confidence: 99%